Critical power, work capacity, and recovery characteristics of team-pursuit cyclists - Pugh, C. F.; Beaven, C. M.; Ferguson, R. A.; Driller, M. W.; Palmer, C. D.; Paton, C. D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Leading a 4-km team pursuit (TP) requires high-intensity efforts above critical power (CP) that deplete riders` finite work capacity (W'), whereas riders following in the aerodynamic draft may experience some recovery due to reduced power demands. This study aimed to determine how rider ability and CP and W' measures impact TP performance and the extent to which W' can reconstitute during recovery positions in a TP race.